Strategy for Improving Smoking Cessation Services in Primary Health Care - Risky Kusuma Hartono; Evita Rosdiana Hutapea (Preventia : The Indonesian Journal of Public Health, 2024)
Amidst the rising numbers of smokers in Indonesia and the increasing burden of smoking-related diseases on the country, the Smoking Cessation Services (SCS) still fail to operate optimally. The aim of this research is to develop a more effective strategy for the SCS model based on the challenges encountered during its implementation. The research method employed qualitative study with a case study approach. The research location was in Depok City, chosen as a national exemplary of SCS. Research period from February to May 2024. Data collection was conducted through in-depth interviews and observations at Community Health Centers who involved in SCS including health professionals, health promotors, and managers. The findings indicate that the SCS is not yet optimal due to insufficiently trained staff, low patient turnout, and failure to achieve the target quit rate. The services still focus on counseling and have not yet incorporated pharmacotherapy. The research concludes that short-term alternative strategies include follow-up calls to patients, establishing telecommunication groups with patients, and reaching out to new patients through schools, while long-term strategies such as program integration and building a telemedicine information system could be implemented to enhance patient visits.